Pembinaan konstruk instrumen penilaian pasca penghunian untuk perumahan bertingkat yang dibina menggunakan kaedah Sistem Binaan Berindustri (IBS) - Musaa, M. K.; A. Rahman, M. A.; H., Nurzalina; Lip, R. (2021)
Post Occupancy Evaluation (POE) is an activity of the building evaluation process with a focus on quality, operational performance and satisfaction of the occupants. The POE is important to evaluate completed and occupied buildings to identify weaknesses and potential for future improvement. To date, there have been various variations of POE instruments and tools to evaluate occupied buildings. However, the POE instrument for assessing high-rise housing constructed using the industrialized building system (IBS) method has not been developed specifically. In this regard, this study aims to discuss the construction of an effective POE instrument to measure the quality and performance of high-rise housing built using the IBS method. For this purpose, the 3 round Delphi method was adapted by involving 15 experts selected based on their background and experience related to IBS. The results of a three-round Delphi study found that 33 out of all sub-constructs were dropped because of low mean scores (<4.2 in two rounds) while 75 sub-constructs were identified as final items. The results of the Delphi study also found that all 10 constructs were 1) Spatial; 2) Design and aesthetics; 3) Physical; 4) Building materials; 5) Quality of work; 6) Comfort and well-being; 7) Environment and health; 8) Maintenance; 9) Value and 10) Cost is the most significant construct for developing PPP instruments. Accordingly, an effective Post-Occupancy Assessment Instrument for measuring the quality, performance and value of a home built using the IBS method should include all of these constructs.